L’impact de la Sélection et du Profil Académique sur la Performance Cognitive D’étudiants Universitaires - Pelletier, Daniel; Larivée, Serge; Coutu, Sylvain; Parent, Sophie (Canadian Journal of Higher Education, 1989)
The assessment of adults by means of Piagetian tests clearly shows that the mastery of formal operations is much less widespread than the theory had led us to believe. Among university students, the discrepancy between performance and expected skills was often attributed to their not being familiar with the contents of the tasks. In this research, another variable which has rarely been taken into account was considered: the selection of candidates for entry into various programs. A sampling of 740 university students majoring in 12 different fields were assessed by means of the Piagetian Logical Operations Test. The data thus collected clearly showed a higher overall performance of students in pure and applied sciences. However, students in more selective social and human science programs produced results comparable with those of students in programs having a high mathematical and/or scientific content, but who were not subjected to a careful selection process. The impact of the selection and grouping of the subjects is discussed. The traditional interpretation of variations in performance in terms of operational deficits is critically examined, and the possible effects on university teaching are presented.